2006
DOI: 10.1038/sj.ijo.0803406
|View full text |Cite
|
Sign up to set email alerts
|

High basal serum allopregnanolone levels in overweight girls

Abstract: Objective: Several studies demonstrated that obese subjects have a hyperactive hypothalamic-pituitary-adrenal axis and that sex steroid hormones have been closely related to the regulation of adiposity, either through direct or indirect physiological mechanisms. Allopregnanolone (3a-hydroxy-5a-pregn-20-one; AP) is a circulating neuroactive steroid hormone involved in the modulation of behavioral functions, stress and neuroendocrine axis. The aim of our study was to evaluate basal serum AP levels in obese child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 49 publications
1
5
1
Order By: Relevance
“…In our study, the PCOS patients had higher allopregnanolone concentrations than both of the control groups. This supports earlier studies that have shown that overweight women have higher baseline allopregnanolone concentrations than normal‐weight women . Other studies have shown that healthy overweight women also have higher allopregnanolone concentrations than normal‐weight healthy controls, although the difference was not significant in our study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our study, the PCOS patients had higher allopregnanolone concentrations than both of the control groups. This supports earlier studies that have shown that overweight women have higher baseline allopregnanolone concentrations than normal‐weight women . Other studies have shown that healthy overweight women also have higher allopregnanolone concentrations than normal‐weight healthy controls, although the difference was not significant in our study.…”
Section: Discussionsupporting
confidence: 88%
“…8 The serum concentrations of allopregnanolone are higher in obese individuals (both men and women) than in normal-weight controls. [9][10][11] However, the treatment of women with PCOS with metformin reduces their allopregnanolone concentrations. 5 Chronic anovulation is very common in PCOS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the prevalence of birth asphyxia was 22.6% in the 1 st minute of birth. This finding is lower compared to a study conducted in Debre Tabor Hospital, Ethiopia (29.9%) [34], Nigeria (30.1%) [11] and a study conducted in Zambia (23%) [9]. In addition, this finding is lower than a review study conducted in Federal Medical Centre, Birnin Kebbi, Nigeria (24.7%) [10].…”
Section: Discussioncontrasting
confidence: 60%
“…In fact, it is well known that obese children are unhappy with their weight and experience more psychosocial distress [36,37]. Unfortunately, we did not evaluate the anxiety levels in our patients; therefore, this hypothesis needs to be confirmed in future studies.…”
Section: Discussionmentioning
confidence: 74%